PARADIGMA STUDI MANAJEMEN BERBASIS MADRASAH DAN GURU PROFESIONAL - Zainur Arifin (Fakultas Tarbiyah Institut Agama Islam Bani Fattah Jombang, 2020)
Abstract: Education is one of the factors that can sustain the survival of a nation. Through education, it is hoped that it will be able to create quality successors of the nation and can make a positive contribution to the life of the nation. However, the current conditions are inversely proportional to the expected conditions. Teachers are one of the important factors in the delivery of education in schools. Increasing the quality of education also means increasing the quality of teachers. Madrasah-based management is a translation of “school based management”. This term first appeared in the United States when people began to question the relevance of education to local problems and the environment. MBM is a new paradigm of education, which provides broad autonomy at the madrasah level (community involvement) in the framework of national education policies. Professional teachers are educators who have the expertise and philosophical skills of Ki Hajar Dewantoro; ing ngarso sung tulodho, ing madya building karso, tut wuri handayani. A teacher who is sufficiently good at the subject matter will guide students, become an example or role model for students and always encourage students to progress. With MBM it has characters that need to be implemented by madrasas that will implement it. the existence of this, a characteristic that distinguishes it from other madrasas. The principles that must be used in implementing MBM are the strength of commitment of the madrasah principal and teachers, the readiness of madrasah resources, the interaction and awareness of all madrasah citizens so that madrasah can have authority and independence in the madrasah organization, madrasahs have the resistance to adapt to change.